Good Corporate Governance Sebagai Implementasi Amanah Dalam Al-Qur’an (Tafsir QS. Al-Mu’minun) - Kusmilawaty, Kusmilawaty; Tarigan, Azhari Akmal; Nasution, Yenni Samri Juliati (ITB AAS INDONESIA Surakarta, 2024)
The article aim is to know how Good Corporate Governance as implementation of trust in QS. Al Mu’minun. The research run by literature studies with qualitative analysis. Source of data this research from documentation studies. The result of study show that trust and promises in Islam are essential to uphold and fulfill if one wishes to be a fortunate and faithful individual. Safeguarding trust in the economic context involves effectively managing the company's resources. This responsible management is referred to as Good Corporate Governance. Based on these principles, the Best Practice Good Corporate Governance in Islam can be formulated to include: Fairness (QS. Al Mu’minun:3), Transparency (QS. Al Mu’minun:3), Accountability (QS. Al Mu’minun:8), and Fulfilling Zakat (QS. Al Mu’minun:4).